Promotion of protected quotas in a province of Argentine Patagonia (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
This article presents an extension experience within the framework of a University in Argentine Patagonia. This consisted of trips to promote the protected geographical and indigenous people quotas, offered by a recently created medical degree. The experience is analyzed from interviews conducted with key institutional actors and seeks to evaluate the experience to frame it in discussions about ways to make the training proposals of public universities more inclusive and diverse, especially those that train professionals for public services, in this case, health.
Keywords: protected quotas; inclusion; medicine; public universities